2000
DOI: 10.1021/ma001161q
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Inverted Phases in Poly(styrene-b-butadiene-b-styrene) Triblock Copolymer by Solvent-Induced Order−Disorder Phase Transition

Abstract: We report observation of inverted phases consisting of spheres and/or cylinders of the majority fraction block in a poly(styrene-b-butadiene-b-styrene) (SBS) triblock copolymer by solventinduced order-disorder phase transition (ODT). The SBS sample has a molecular weight of 140K Da and a polystyrene (PS) weight fraction of 30%. Tapping mode atomic force microscopy (AFM) and transmission electron microscopy (TEM) were utilized to study the copolymer microstructure of a set of solution-cast SBS films dried with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(132 citation statements)
references
References 37 publications
8
123
1
Order By: Relevance
“…Since the inter-block repulsion decreases with increasing temperature, it is often possible to identify an order- disorder transition temperature (ODT). An order-disorder transition can also be induced by applying a stress-in this case a shear-thinning is observed (25Ϫ27, 29Ϫ32)-or in solutions, by varying the solvent concentration (33,34). In PMA for roofing membranes containing high percentages of SBS (up to 15 wt%), Fawcett and co-workers (35) observed an extensive network created by the polystyrene domains, which is effective even above their glass transition temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Since the inter-block repulsion decreases with increasing temperature, it is often possible to identify an order- disorder transition temperature (ODT). An order-disorder transition can also be induced by applying a stress-in this case a shear-thinning is observed (25Ϫ27, 29Ϫ32)-or in solutions, by varying the solvent concentration (33,34). In PMA for roofing membranes containing high percentages of SBS (up to 15 wt%), Fawcett and co-workers (35) observed an extensive network created by the polystyrene domains, which is effective even above their glass transition temperature.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that several types of phase separation patterns are formed using SBS films depending on the evaporation speed of the solvent [199]. Figure 65 shows typical (a) topographic and (b) phase images obtained simultaneously at a rate of 84 ms/frame in distilled water.…”
Section: Compositional Mapping On Blended Polymersmentioning
confidence: 99%
“…[21][22][23]30 Thus, from the calculation of interaction parameters, it is seen that CHX used in this study is a θ-solvent for PS blocks and a good solvent for PBD blocks while HX is a selective solvent for only PBD blocks. Hence, CHX can provide a higher degree of swelling for PBD blocks than for PS blocks.…”
Section: Methodsmentioning
confidence: 82%
“…They showed that slightly different affinities of solvents for blocks could dramatically affect their morphologies. 21,22,30 Moreover, the affinity of solvents for polymers is changeable in a given system. Therefore, it is essential to consider the relative affinity of solvents for BCPs systematically.…”
Section: Methodsmentioning
confidence: 99%